Market Analysis of NFT Integration in Video Games - Hasibuan, Muhammad Said; Putra, Arie Setya; Syarif, Admi; Mahfut; Sulistiyanti, Sri Ratna (Bright Publisher, 2025)
The integration of Non-Fungible Tokens (NFTs) into the gaming industry has introduced a novel economic model, reshaping monetization strategies and player engagement. This paper analyzes the market potential of NFT integration in video games through a comprehensive approach combining market segmentation, trend analysis, and predictive modeling. Using historical sales data from various genres and platforms, the research identified key segments that show high potential for NFT adoption, particularly action, role-playing, and sports games on mainstream platforms such as PlayStation and Xbox. The market segmentation, achieved through K-Means clustering, revealed distinct groups of video games based on genre, platform, and regional sales performance. Trend analysis using time series models like ARIMA and Prophet highlighted emerging and declining popularity across different genres and platforms. The study also applied predictive modeling techniques, including Random Forest and Gradient Boosting, to forecast the potential success of NFTs in specific game genres. The models demonstrated strong performance, with low mean absolute error (MAE) and root mean squared error (RMSE), confirming that high-engagement genres are likely to benefit most from NFT integration. The findings suggest that NFTs can enhance player experiences by offering unique, tradable in-game assets, thus creating new revenue streams for developers. The paper concludes by recommending strategies for NFT implementation, targeting high-potential genres and platforms, and addressing regional market preferences. Limitations related to data constraints and emerging trends are discussed, and future research directions are proposed, focusing on consumer sentiment analysis and real-world case studies of NFT integration in video games.